2019
DOI: 10.1002/jcp.29320
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐2 and Na+/H+ exchanger isoform 1 modulate the efficiency of renal cell migration

Abstract: Aquaporin-2 (AQP2) promotes renal cell migration by the modulation of integrin β1 trafficking and the turnover of focal adhesions. The aim of this study was to investigate whether AQP2 also works in cooperation with Na + /H + exchanger isoform 1 (NHE1), another well-known protein involved in the regulation of cell migration.Our results showed that the lamellipodia of AQP2-expressing cells exhibit significantly smaller volumes and areas of focal adhesions and more alkaline intracellular pH due to increased NHE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The authors propose that the interaction between AQP2 and integrin β1 modulates integrin trafficking and turnover at focal adhesion sites, thereby contributing to cell migration. We recently confirmed that the presence of AQP2 on the plasma membrane promotes cell migration in association with TRPV4 (Di Giusto et al, 2019).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The authors propose that the interaction between AQP2 and integrin β1 modulates integrin trafficking and turnover at focal adhesion sites, thereby contributing to cell migration. We recently confirmed that the presence of AQP2 on the plasma membrane promotes cell migration in association with TRPV4 (Di Giusto et al, 2019).…”
Section: Discussionmentioning
confidence: 58%
“…We then look for potential implications of ATPe modulation of P2 receptors in AQP2‐expressing cells. Having in mind that we recently published that AQP2 together with TRPV4 accelerates cell migration (Di Giusto et al, 2019), as well as compelling evidence, demonstrating that calcium and ATP act as a coordinating second messenger in this process (Jiang, Mousawi, Yang, & Roger, 2017), we investigated the modulation of purinergic signaling in cell migration of WT‐RCCD 1 and AQP2‐RCCD 1 cells by using the wound healing assay (Figure S6). Figure 7 shows, as we previously informed, that cells‐expressing AQP2 migrate faster than WT‐RCCD 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In migrating cells, NHE1 localizes at the leading edge of lamellipodia and coordinates with various ion channels to in uence cell polarity and directional migration by promoting sodium in ux and regulating cytoskeletal dynamics. Previous research has found that AQP2-mediated Ca 2+ -dependent NHE1 activation is associated with migration in rat renal cortical collecting duct epithelial cells [30]. Furthermore, NHE1 located at the rear of lamellipodia accelerates the movement of these cells, providing collective driving forces for MDCK cell migration [26,31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to channels that directly transport Ca 2+ , Ca 2+ is a second messenger that often regulates the activity of various ion channels and transporters (Mahnensmith and Aronson, 1985 ; Garty and Palmer, 1997 ; Ruiz et al, 1999 ; Shieh et al, 2000 ). For example, the activity of NHE1 can be modulated by Ca 2+ through TRPV4, determining pH-dependent actin polymerization, providing mechanical stability to delineate lamellipodia structure, and defining the efficiency of cell migration (Di Giusto et al, 2020 ). Ca 2+ also affects the structure and dynamics of the cytoskeleton (Oertner and Matus, 2005 ; Hepler, 2016 ; Zhao et al, 2019 ; Maity et al, 2020 ), which further impacts the distribution and function of ion channel (Levina et al, 1994 ; Steele and Fedida, 2014 ; Vallés et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%